(untitled) (Journal of Social Sciences Review, 2025)
Adolescents are highly engaged in the digital world is evident from the growth of the cyberbullying problems in urban settings. Online abuse can cause depression, anxiety, stress, and low self-esteem. Nevertheless, few studies have examined its effects on secondary school students in Pakistan. This study explores the psychological impact of cyberbullying on secondary school students (n=441) in urban Pakistan, specifically its association with psychological distress and self-esteem. A cross-sectional design conducted on 300 students using purposive sampling. Data were gathered via the Cyberbullying Victimization Scale, the Depression, Anxiety, and Stress Scale (DASS-21), and the Rosenberg Self-Esteem Scale. Statistical analyses of these variables were performed in SPSS Version 28 (IBM Corp. Released 2021. IBM SPSS Statistics for Windows, Version 28.0. Armonk, NY: IBM Corp). Cyberbullying was strongly associated with depression (r=0.48, p<.001), anxiety (r=0.51, p <.001), depression (r=.001), and negatively associated with stress (r=0.46, p<.001). The results indicated a negative correlation between self-esteem and cyberbullying (r=-0.39, p<.001). Psychological distress partially mediated the association between cyberbullying and self-esteem according to mediation analysis. Cyberbullying has a serious impact of students’ mental health. Schools must conduct awareness campaigns, foster digital literacy, and introduce psychological interventions.